Effects of Transapical Transcatheter Mitral Valve Implantation - Hsiung, Ming-Chon; Yin, Wei-Hsian; Lee, Yung-Tsai; Tsao, Tien-Ping; Lee, Kuo-Chen; Huang, Kuan-Chih; Chen, Pei-En; Chiang, Wei-Hsuan; Tung, Tao-Hsin; Wei, Jeng (Frontiers in Cardiovascular Medicine, 2021)
Purpose. In this study, transapical transcatheter mitral valve-in-valve implantation (TAMVI) was compared with surgical redo mitral valve replacement (SRMVR) in terms of clinical outcomes. Methods. We retrospectively identified patients with degenerated mitral bioprostheses or failed annuloplasty rings who underwent redo SRMVR or TAMVI at our medical center. Clinical outcomes were based on echocardiography results. Results. We retrospectively identified patients with symptomatic mitral bioprosthetic valve dysfunction (n=58) and failed annuloplasty rings (n=14) who underwent redo SRMVR (n=36) or TAMVI (n=36). The Society of Thoracic Surgeons Predicted Risk of Mortality scores were higher in the TAMVI group (median: 9.52) than in the SRMVR group (median: 5.59) (P-value=0.02). TAMVI patients were more severe in New York Heart Association (P-value=0.04). The total procedure time (skin to skin) and length of stay after procedures were significantly shorter in the TAMVI group, and no significant difference in mortality was noted after adjustment for confounding factors (P-value= 0.11). The overall mean mitral valve pressure gradient was lower in the TAMVI group than in the SRMVR group at 24 months (p<0.01). Both groups presented a decrease in the severity of mitral and tricuspid regurgitation at 3 to 24 months. Conclusions. In conclusion, the statistical analysis is still not robust enough to make a claim that TAMVI is an appropriate alternative. The outcome of the patient appears only to be related to the patient's pre-operative STS score. Additional multi-center, longitudinal studies are warranted to adequately assess the effect of TAMVI.